WHAT DO PHYSIOTHERAPY AND REHABILITATION STUDENTS THINK ABOUT ONLINE LEARNING DURING THE PANDEMIC? - DOĞRU HÜZMELİ, Esra; TUĞRAL, Yağmur; GÖKÇEK, Özden; KAVVASOĞLU, Itır; FİLİZ, Muhammet Şehmus; PAZARBAŞI, Batın; ÇİFT, Fatma Eda; BAYTAK, Sevgi; LEKESİZ, Eren; BEZGİN, Sabiha (Turkish Journal of Physiotherapy Rehabilitation, 2022)
Purpose: Online learning is a comprehensive type of education in which the teacher and the student are physically separated. We wanted to know how online learning was evaluated through the view of physiotherapy and rehabilitation students. Methods: We included 283 students from department of physiotherapy and rehabilitation in the study. A questionnaire that consisted of 45 multiple-choice questions and 2 open-ended questions was applied to the students. The questions involved whether the student has previously participated in any online learning program, has had access to online learning and technical problems experienced during access. Results: Our study included 210 (74.20%) women and 73 (25.80%) men. We questioned status of having online learning before the pandemic and 49.82% of the students reported that they did not receive online learning before. We found that 21.55% of the students could not motivate themselves. 30.39% of the students thought having insufficient education in the practical courses due to online education. 10.25% of the students stated that they could not access the necessary equipment for online learning. In the question about they received high-quality education with online learning; 21.55% of the students stated that they did not agree at all. Conclusion: We think that it is more beneficial to give some theoretical courses online and synchronized, and practical courses face to face. Therefore, we think that it will be beneficial to postpone the practical courses that cannot be done face to face due to the pandemic and to give those courses face to face after the pandemic process.